Social exclusion, cognition, and emotion - Tragesser, Sarah Louise, author; Barrett, Karen C., advisor; Aloise-Young, Patricia A., advisor; Littrell, John M., committee member; Swaim, Randall C., committee member; Beauvais, Frederick, committee member (Colorado State University. Libraries, 2005)
Being included in social groups has been important to human survival throughout evolutionary history, and has probably evolved as an important human need (Baumeister & Leary, 1995). While research suggests that exclusion is highly detrimental (e.g., Leary, Kowalski, Smith, & Phillips, 2003), more experimental research is needed to specify the emotional and cognitive effects. The purposes of the present research were to 1) identify specific emotion effects of exclusion, 2) test whether the experience of activating (e.g., anger) vs. withdrawal (e.g., sadness) emotions accounts for emotion-induced deficits in cognitive processing, 3) test whether the content of information (social versus non-social) affects processing among excluded participants, and 4) test these issues across higher-order processing tasks (e.g., comprehension) and memory tasks (i.e., recall of events from hypothetical diary entries). Method: Fifty-nine male and 67 female undergraduate psychology students received bogus feedback from a personality test predicting one of the following: they would be surrounded by loved ones (inclusion), alone in life (exclusion), or accident-prone (negative control). Participants then completed self-report measures of emotions and action tendencies, reading comprehension tasks, and the memory task. Analyses: ANOVAs and MANOVAs were conducted to test the effects of the manipulation on each emotion. Next, ANCOVAs were used to test the effects of gender, content of comprehension materials (passages or diary entries), and condition on cognitive performance (i.e., correct answers on comprehension task or number of diary entries recalled) covarying for each specific emotion. Results and Conclusions: First, exclusion produced the most post-experimental relief, and anger (an activating emotion) was /ess common in the exclusion condition. Second, when relief was controlled, participants in the exclusion condition showed poorer comprehension in general, and when other emotions were controlled, excluded males showed poorer comprehension of the social passage, partially supporting previous research (Baumeister, Twenge, & Nuss, 2002). Third, diary entry findings showed evidence for mood congruent memory, such that except when controlling for relief, alone-in-life participants recalled more negative than positive events.
Keywords: social psychology